2022
DOI: 10.3390/jcm11164904
|View full text |Cite
|
Sign up to set email alerts
|

Normal References of Peak Oxygen Uptake for Cardiorespiratory Fitness Measured with Cardiopulmonary Exercise Testing in Chinese Adults

Abstract: Introduction: This study aims to establish normal reference values of peak oxygen uptake (VO2peak) for cardiorespiratory fitness (CRF) in Chinese adults using cardiorespiratory exercise testing (CPET). Methods: A cross-sectional study was done in four communities, two in the North (Beijing) and two in the South (Hezhou, Guangxi) of China from 1 January 2017 to 31 December 2018, with one urban and one rural in each region. Out of 1642 participants screened, 1114 were eligible and completed CPET using a cycle er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Compared with the CPX parameters based on the cycle ergometer for Chinese adults,12 the relative V˙O 2peak based on treadmill was notably higher in all age groups. The mean differences of V˙O 2peak ranged from 6.8-15.6 mL/kg/min, consistent with the findings of other reports 8,13…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Compared with the CPX parameters based on the cycle ergometer for Chinese adults,12 the relative V˙O 2peak based on treadmill was notably higher in all age groups. The mean differences of V˙O 2peak ranged from 6.8-15.6 mL/kg/min, consistent with the findings of other reports 8,13…”
Section: Discussionmentioning
confidence: 66%
“…[7][8][9] These reference standards can be used to compare CRF relative to peers and as an aide for clinical decision-making.A systematic review in 2019 showed that CRF reference standards were established in 29 studies (nine from North America, four from South America, and 16 from Europe, without relative data from the general Asian population). 10 Dun et al 12 and Wang et al 12 successively provided reference values for CRF measured with CPX in Chinese adults from relatively small sample sizes (n = 964 and n =1114). However, in China treadmill-based CPX is widely applied.…”
mentioning
confidence: 99%